2023
DOI: 10.3390/biomedicines11041126
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Complex Relationship between Diabetes and Cardiovascular Complications: Understanding Diabetic Cardiomyopathy and Promising Therapies

Abstract: Diabetes mellitus (DM) and cardiovascular complications are two unmet medical emergencies that can occur together. The rising incidence of heart failure in diabetic populations, in addition to apparent coronary heart disease, ischemia, and hypertension-related complications, has created a more challenging situation. Diabetes, as a predominant cardio-renal metabolic syndrome, is related to severe vascular risk factors, and it underlies various complex pathophysiological pathways at the metabolic and molecular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 182 publications
(197 reference statements)
0
4
0
Order By: Relevance
“…The role of CADD in cardiovascular diseases : Cardiovascular diseases (CVD) are considered the first cause of death globally 178 . It is common to have significant coronary heart disease, myocardial ischemia and hypertension, as well as diabetes-related complications 179 . Early scientists used CADD technology applied to cardiovascular disease research and successfully discovered the ACE1 inhibitor captopril 124 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of CADD in cardiovascular diseases : Cardiovascular diseases (CVD) are considered the first cause of death globally 178 . It is common to have significant coronary heart disease, myocardial ischemia and hypertension, as well as diabetes-related complications 179 . Early scientists used CADD technology applied to cardiovascular disease research and successfully discovered the ACE1 inhibitor captopril 124 .…”
Section: Discussionmentioning
confidence: 99%
“…In cases of MCR (Mucocutaneous Candidiasis and Reticuloendotheliosis) and diabetes, fungal infections primarily affect the rhino-orbital-cerebral region and the cutaneous and pulmonary areas. In diabetic patients, the invasive fungal infection shows significant aggressive signs, including facial pain and purulent nasal discharges ( 60 , 61 ). Thus, the complications associated with diabetes related mycosis are challenging to address via conventional antiviral therapies ( 62 ).…”
Section: Risk Factors For Individuals Prone To Fungal Diseasementioning
confidence: 99%
“…43 The NF-κB response triggered by lipopolysaccharide in monocytes and dendritic cells serves as a phenotypic characteristic and a potential indicator of pathogenic processes in human T1D. 47 In animal murine models of T1D, it has been observed that TNF receptor-associated factor 6 (TRAF6) plays a mediating role in endothelial damage induced by high glucose levels, and this process is governed by signaling pathways involving NF-κB and AP-1. 48,49 In human monocytic lymphocytes, miRNA-146a, a transcriptional product of the LOC285628 gene situated on the 5th chromosome, is responsive to lipopolysaccharide (LPS) stimulation.…”
Section: Type I Diabetesmentioning
confidence: 99%